Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/febs.12662
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐activating factor downregulates the expression of liver X receptor‐α and its target genes in human neutrophils

Abstract: Liver X receptors (LXRs) are ligand-activated members of the nuclear receptor superfamily that regulate the expression of genes involved in lipid metabolism and inflammation, although their role in inflammation and immunity is less well known. It has been reported that oxysterols/LXRs may act as anti-inflammatory molecules, although opposite actions have also been reported. In this study, we investigated the effect of platelet-activating factor (PAF), a proinflammatory molecule, on LXRa signalling in human neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
1
0
1
Order By: Relevance
“…39 The stimulation of LXRα by its synthetic agonist (TO901317) induces a decrease in ROS levels produced in human neutrophils. 12,40 The behavior of naringenin is different to that observed by us with other LXRα stimulators. We have reported previously that he status redox cellular is essential for the activity LXRα.…”
Section: Molecular Pharmaceuticscontrasting
confidence: 58%
See 1 more Smart Citation
“…39 The stimulation of LXRα by its synthetic agonist (TO901317) induces a decrease in ROS levels produced in human neutrophils. 12,40 The behavior of naringenin is different to that observed by us with other LXRα stimulators. We have reported previously that he status redox cellular is essential for the activity LXRα.…”
Section: Molecular Pharmaceuticscontrasting
confidence: 58%
“…Pro-oxidant molecules inhibit LXRα production and antioxidant compound reverted this effect and even enhanced LXRα expression. 12,40 In this article we detected that a pro-oxidant stimuli, naringenin, induced a clear LXRα and target genes stimulation, this effect had been previously detected by us in neutrophils with other strong prooxidant agents at high concentrations, platelet-activating factor (PAF) and H 2 O 2 . 41 We concluded that a low ROS production inhibited LXRα expression but high ROS production induced LXRα and target genes mRNA expression.…”
Section: Molecular Pharmaceuticssupporting
confidence: 57%